Electronic Communication between two [10]cycloparaphenylenes and Bis(azafullerene) (C59N)2 Induced by Cooperative Complexation. Issue 23 (7th May 2018) - Rio, Jérémy; Beeck, Sebastian; Rotas, Georgios; Ahles, Sebastian; Jacquemin, Denis; Tagmatarchis, Nikos; Ewels, Chris; Wegner, Hermann A.
Abstract: The complex of [10]cycloparaphenylene ([10]CPP) with bis(azafullerene) (C59 N)2 is investigated experimentally and computationally. Two [10]CPP rings are bound to the dimeric azafullerene giving [10]CPP⊃(C59 N)2 ⊂[10]CPP. Photophysical and redox properties support an electronic interaction between the components especially when the second [10]CPP is bound. Unlike [10]CPP⊃C60, in which there is negligible electronic communication between the two species, upon photoexcitation a partial charge transfer phenomenon is revealed between [10]CPP and (C59 N)2 reminiscent of CPP‐encapsulated metallofullerenes. Such an alternative electron‐rich fullerene species demonstrates C60 ‐like ground‐state properties and metallofullerene‐like excited‐state properties opening new avenues for construction of functional supramolecular architectures with organic materials. Abstract : Communications skills : The photophysical and redox properties of the complex of two [10]cycloparaphenylenes ([10]CPPs) with bis(azafullerene) (C59 N)2 support an electronic interaction between the components. This supramolecular organic fullerene assembly demonstrates C60 ‐like ground‐state properties and metallofullerene‐like excited‐state properties opening new avenues for organic materials.